One year record of bioaerosols and particles concentration in Indo-Gangetic Plain: Implications of biomass burning emissions to high-level of endotoxin exposure. (May 2017) - Rajput, Prashant; Anjum, Manzar Hussain; Gupta, Tarun
Abstract: Previous studies worldwide have suggested the potential role of bioaerosols as ice-nuclei and cloud-condensation nuclei. Furthermore, their participation in regulating the global carbon cycle urges systematic studies from different environmental conditions throughout the globe. Towards this through one-year study, conducted from June 2015–May 2016, we report on atmospheric abundance and variability of viable bioaerosols, organic carbon (OC) and particles number and deduced mass concentrations from Indo-Gangetic Plain (IGP; at Kanpur). Among viable bioaerosols, the highest concentrations of Gram-positive bacteria (GPB), Gram-negative bacteria (GNB) and Fungi were recorded during December–January (Avg.: 189 CFU/m 3 ), November (244 CFU/m 3 ) and September months (188 CFU/m 3 ), respectively. Annual average concentration of GPB, GNB and Fungi were 105 ± 58, 144 ± 82 and 116 ± 51 CFU/m 3 . Particle number concentration (PNC) associated with fine-fraction aerosols (FFA) predominates throughout the year. However, mineral dust (coarser particle) remains a perennial constituent of atmospheric aerosols over the IGP. Temporal variability records and significant positive linear relationship (p < 0.05) of GPB and GNB with OC and biomass burning derived potassium (K + BB ) indicates their association with massive emissions from paddy-residue burning (PRB) and bio-fuel burning. Influence of meteorological parameters on viable bioaerosols abundance has been rigorously investigated herein. Accordingly, ambient temperature seems to be more affecting the bacteria (anti-correlation), whereas wet-precipitation (1–4 mm) relates to higher abundance of Fungi. High abundance of GNB during large-scale biomass burning emissions has implications to endotoxin exposure on human health. Field-based data-set of bioaerosols, OC, PNC and deduced mass concentrations reported herein could serve to better constraint their role in human health and climate relevance. Graphical abstract: Highlights: Highest concentration of GNB was recorded during November (244 CFU/m 3 ). Mineral dust remains a perennial constituent of atmospheric aerosols in IGP. Origin of GPB and GNB from BB is inferred from correlation with OC and K + BB . Abstract : Biomass burning emissions intensification period overlaps with higher concentrations of fine PM and GNB, a source of endotoxin in ambient air.